2020
DOI: 10.1016/j.jmir.2020.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose from digital breast tomosynthesis screening – A comparison with full field digital mammography

Abstract: Objectives: To compare Mean Glandular Dose (MGD) and effective dose from digital breast tomosynthesis (DBT) screening with that from full field digital mammography (FFDM) screening. Method: To simulate compressed breasts, two Perspex-polyethylene breast phantoms were used, one phantom for compressed breast in craniocaudal and the other for compressed breast in mediolateral oblique. An adult ATOM dosimetry phantom was loaded with high sensitivity thermoluminescence dosimeters; the phantom was then positioned on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…According to the study by O'Connell et al 11 reported a non‐significantly improvement in glandular dose for DBT versus CBBCT with 6.5 ± 2.9 and 8.2 ± 1.4 mGy for CBBCT with 21% dose reduction for DBT. M.Ali et al 48 also reported a dose of 3.6 mGy for DBT versus 2.8 mGy for DM, indicating a 22% dose increment over DM. It can be deduced that CBBCT tends to have a higher glandular dose compared to DBT, making DBT a more radiation‐efficient imaging modality.…”
Section: Discussionmentioning
confidence: 97%
“…According to the study by O'Connell et al 11 reported a non‐significantly improvement in glandular dose for DBT versus CBBCT with 6.5 ± 2.9 and 8.2 ± 1.4 mGy for CBBCT with 21% dose reduction for DBT. M.Ali et al 48 also reported a dose of 3.6 mGy for DBT versus 2.8 mGy for DM, indicating a 22% dose increment over DM. It can be deduced that CBBCT tends to have a higher glandular dose compared to DBT, making DBT a more radiation‐efficient imaging modality.…”
Section: Discussionmentioning
confidence: 97%
“…It has high sensitivity and specificity. The average effective dose from one lung cancer screening CT is less than 1.0 mSv [19] compared to a standard four-view digital mammography with an average effective dose of 0.68 mSv [20]. Many patients have additional magnification and/or spot compression images or tomosynthesis for the workup of an abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…• The MGD has been used as an indicator of radiation risk in DBT or DM, and MGD is fundamentally related to the target/filter combination, kV, breast density (glandularity) and breast size (compressed breast thickness) [28,29]. Therefore, the choice of 2.0 mGy as MGD was taken as a parameter for a certain breast thickness and target/filter combination.…”
Section: Justifying the Estimated Risk Of Radiation-induced Cancer In...mentioning
confidence: 99%